Gender Diversity and Firm Performance: Evidence from Pakistan’s Industrial and Services Sectors - Kiani, Maira; Falki, Nuzhat; Habib, Saira (Journal of Development and Social Sciences, 2025)
This study examines the impact of gender diversity on organizational performance across the industrial and services sectors in Pakistan. Utilizing the Resource-Based View, Agency Theory, and Institutional Theory, it examines the impact of female involvement in ownership, management, and workforce positions on organizational results, specifically firm sales. This research seeks to empirically assess if and how gender-inclusive enterprises in Pakistan, characterized by female labor force participation and sector-specific gender inequities, outperform their counterparts. The study utilized Propensity Score Matching (PSM) with firm-level data from the World Bank Enterprise Survey (2022) to mitigate selection bias and discern causal effects. Three treatment dimensions were examined: female ownership, female executive leadership, and female worker representation. Each treated firm was paired with observationally comparable non-treated enterprises through the nearest-neighbor matching. The dependent variable was company performance, represented by the logarithm of sales. The results demonstrate that companies with female managers, and female workers achieved superior performance. Female ownership was not strongly correlated with statistically significant increases in the logarithm of sales, even after matching. These findings emphasize that gender-diverse companies are both socially progressive and commercially beneficial.